Trends in postgraduate professional orientation of young doctors graduated from the Medical University-Sofia - Vidin Kirkov (Pharmacia)
Professional choice is a complex decision-making process, determined by social and personal factors, as it is driven not only by the needs of society but also by the interests, opportunities, needs, and inclinations of the individual. In view of this, this article will present and analyze data from an empirical study examining trends in the professional orientation of young doctors who have graduated from the Medical University-Sofia in 2021, 2022, and 2023.